Radiocarbon and U-series age constraints for the Lateglacial rock art of Sicily - Di Maida, G. (2020)
The presence of rock and portable art on Sicily has been recognized since World War II. This record has been unanimously attributed to the Upper Palaeolithic in the published literature, based almost uniquely on stylistic reasoning. Here we present the first absolute dates in direct association with the Sicilian art record. These data provide new insights into the life of Southern European hunter-gatherers and their relationships with coeval groups from Western Europe, contributing a fresh perspective on the ongoing discussion about the development and co-existence of different art traditions in Europe during the final phases of the Pleistocene and at the beginning of the Holocene.